A Typology of Situations of Accounting Systems Integration - Lazhar El Orf (Journal of Accounting and Management Information Systems (JAMIS), 2012)
This paper presents the first results of a qualitative research about the organization of the Accounting Information Systems (AIS) of four companies operating in different contexts (two medium-sized and two large companies). Our study's main objective is to contribute to the understanding of the determinants of the integration of accounting information systems. It shows that the strategy is, beyond all other considerations, the primary determinant of integration practices of accounting systems of the companies surveyed, followed by the size and elements of context such as the system of management control. Organizations whose activities are not diversified (or monoactivity) opt more for accounting systems partially integrated or stand-alone while those whose activities are diversified prefer more diversified integrated accounting systems whose design is based on event-based approach and multidimensional accounting (Sorter 1969). The integration of accounting subsystems seems to be part of the mechanisms developed by diverse organizations to manage / control their very different structures. Hence, the theory of differentiation-integration (Lawrence and Lorsch 1969) explains very well the practical integration of accounting systems observed. Our study leads to a typology of modes of integration of accounting systems: (1) multidimensional, (2) integrated, (3) partially integrated, (4) autonomous.
Keywords: M15; 650; Theory of differentiation-integration; event-based approach; multidimensional system; integrated system; partially integrated system; autonomous system